2023
DOI: 10.3390/nu15041012
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chosen Essential Elements (Zn, Cu, Se, Fe, Mn) in Food for Special Medical Purposes (FSMPs) Dedicated to Oncology Patients—Critical Review: State-of-the-Art

Abstract: The scoping review aimed to characterise the role of selected essential elements (Zn, Cu, Se, Fe, Mn) in food for special medical purposes (FSMPs) aimed at oncology patients. The scope review was conducted using Scopus, Google Scholar, and Web of Science to find published references on this subject. Data from the reviewed literature were related to the physiological functions of the element in the body, and the effects of deficiencies and excesses, referring to the latest ESPEN and EFSA guidelines, among other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 154 publications
(174 reference statements)
0
13
0
Order By: Relevance
“…represents dependence of concentrations on the sampling sites with different anthropogenic loadings (see Table 1, 3) Interactions between trace elements observed in the plants themselves show that they can be either antagonistic or synergistic. The largest number of antagonistic reactions is noted for Fe, Mn, Co, and Zn, which are key elements in plant physiology [68][69][70]. The functions of these elements are associated with absorption processes and with enzymatic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…represents dependence of concentrations on the sampling sites with different anthropogenic loadings (see Table 1, 3) Interactions between trace elements observed in the plants themselves show that they can be either antagonistic or synergistic. The largest number of antagonistic reactions is noted for Fe, Mn, Co, and Zn, which are key elements in plant physiology [68][69][70]. The functions of these elements are associated with absorption processes and with enzymatic reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Iron is one of the most copious elements, 9 and is an essential biological element for all living creatures. 10,11 It has a lot of biological adaptability, which shows itself as oxidation-reduction reaction, 12 but due to all the abundance of iron in the earth, it is known as a limiting factor for growth. 9 This contradiction is based on the fact that the combination of iron with oxygen produces highly insoluble oxides, which are not readily available for the absorption of living organisms.…”
Section: The Characteristics and Role Of Iron In Human Healthmentioning
confidence: 99%
“…Some writers believe that FSMPs intended for oncology patients may not be adequate for some critical elements, such as Zn, Cu, Se, Fe, or Mn, despite the regulatory standards regarding the composition of FSMPs, implying that the formulations are based on commonly accepted scientific facts [7]. In addition, similar studies have indicated that sample determination for Se, Zn, K, Mg, and vitamin C differ from (E.U.)…”
Section: Understanding Fsmp Composition and Labelling Requirementsmentioning
confidence: 99%